2017
DOI: 10.1038/nphys4258
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Chlamydomonas microalgae to surfaces is switchable by light

Abstract: Although microbial responses to light have been widely recognized, any influence of light on cell-surface interactions remains elusive. Here, we reveal that the unspecific adhesion of microalgae to surfaces can be reversibly switched on and o by light. Using a micropipette force spectroscopy technique, we measured in vivo single-cell adhesion forces and show that the microalga's flagella provide light-switchable adhesive contacts with the surface. This light-induced adhesion to surfaces is an active and comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(138 citation statements)
references
References 36 publications
3
135
0
Order By: Relevance
“…26,27 In a previous study, we report on our discovery that the flagella-mediated adhesion of Chlamydomonas to surfaces can be reversibly switched on and off by light. 28 We showed that the adhesion force of up to several nanonewton in white light is reduced to zero in red light conditions. Although we were able to identify light as a key requirement for the surface colonization, the intermolecular interactions that govern the adhesion of Chlamydomonas to surfaces remained elusive.…”
mentioning
confidence: 79%
“…26,27 In a previous study, we report on our discovery that the flagella-mediated adhesion of Chlamydomonas to surfaces can be reversibly switched on and off by light. 28 We showed that the adhesion force of up to several nanonewton in white light is reduced to zero in red light conditions. Although we were able to identify light as a key requirement for the surface colonization, the intermolecular interactions that govern the adhesion of Chlamydomonas to surfaces remained elusive.…”
mentioning
confidence: 79%
“…A thin slab of silicon cut from a wafer (type P/Bor, orientation 100 , resistivity 120 Ωcm, unilateral polished, Si-Mat, Germany) has been glued onto a custom-made stainless steel substrate holder with PDMS. Substrate [30,33]. The micropipette cantilever, furnished with a tube and syringe filled with deionised water, was mounted onto a 3axis piezo-driven manual micromanipulator (PCS-5400, Burleigh, Thorlabs, USA) and inserted into the liquid cell.…”
Section: Methodsmentioning
confidence: 99%
“…In principle, forces can be measured simultaneously through the deflection of the micropipette. However, previous works utilizing such micropipette force sensors [30][31][32][33][34][35][36] were limited to quasistatic measurements. In this case the damping of the micropipette cantilever by hydrodynamic drag forces remains negligible, and forces can be directly recovered from the cantilever deflection and its static spring constant.…”
Section: Introductionmentioning
confidence: 99%
“…[79] However, these may influence factors such as adherence of the cells to the anode, cell-cell connection in a biofilm, and phototaxis. [79,80] They may therefore have an effect on DEET without being directly involved in the electron transfer pathway.…”
Section: Endogenous Eet Mechanismsmentioning
confidence: 99%